Public Goods, Common Inputs, and the Efficiency of Full Allocations. - Cohen, Susan I.; Loeb, Martin (The Accounting Review, 1982)
ABSTRACT: This paper addresses the simultaneous problems of determining input levels in a multidivisional firm and allocating the input costs to the divisions. A distinction analogous to that in economics between pure public goods and pure private goods is made between pure common inputs and pure private inputs. It is shown that for a pure common input, decentralization utilizing a full cost allocation can result in an efficient allocation of the input. Although efficient decentralization is possible in this case, the "free-rider problem" suggests that such an outcome is unlikely. In addition, it is shown that recently suggested allocation schemes based on game-theoretic concepts may not lead to an efficient allocation of pure common inputs.